Iodine doped graphene as anode material for lithium ion battery. (November 2015) - Zhan, Yunfeng; Zhang, Bodong; Cao, Linmin; Wu, Xiaoxian; Lin, Zhipeng; Yu, Xiang; Zhang, Xiaoxue; Zeng, Dongrong; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Meng, Hui
Abstract: I-doped graphene is synthesized by a facile heat treatment method and used as anode material for lithium ion battery. The doped graphene exhibits high reversible capacity (1690 mAh g −1 at 100 mA g −1 ), good cyclability (retaining 92.6% reversible capacity after 200 cycles) and excellent rate performance compared with undoped graphene. The superior electrochemical performance of the I-doped graphene is explained by the change of graphene lattice, defects and positive charge density introduced by the doping of I atoms.